KOMPETENSI GURU KELAS DALAM MENGEMBANGKAN RANAH AFEKTIF SISWA MIN SIBUHUAN - Ulfa Khoiriyah Siregar; Abd. Manap HT. Uruk; Irma Sari Daulay (CV. ADIBA AISHA AMIRA, 2023)
The aim of this research is to determine (1) the competence of class teachers in developing students' affective domain at MIN Sibuhuan and (2) strategies for developing students' affective domain at MIN Sibuhuan. This research is a type of field research, where this research is carried out by conducting a survey directly to the research object. The subjects and research objects as data sources in this research were used as samples in this research, namely 27 MIN Sibuhuan teachers, students and documentation. The results of this research show that the competence of class teachers in developing the affective domain of students at MIN Sibuhuan is through the role of educators which can be used in learning affective aspects in the field of Aqidah Akhlak using traditional strategies, namely by providing advice or indoctrination. In other words, this strategy is pursued by telling directly which values are good and which are not good. With this strategy, the teacher has a decisive role, because goodness/truth comes from above, and students just have to accept that goodness/truth without having to question its nature. Implementing this strategy will result in students only knowing and memorizing certain types of good and bad values, and not necessarily implementing them. The strategy for developing the affective domain of students at MIN Sibuhuan is carried out at the MIN Sibuhuan mosque through various techniques such as indoctrination, starting value learning by destroying the values that already exist within the students or their personalities to disrupt them, so that they no longer have a stance, for example by asking questions and answers. , interview. When the student's mind is empty and his rational consciousness is no longer able to control himself, and his stance has been lost, he continues with the second stage; namely the stage of instilling fanaticism, namely that educators are obliged to instill new ideas that are considered correct so that the values they instill enter children without going through established rational considerations. The role of instilling fanaticism uses an emotional approach rather than a rational approach, for example love of the country. If students are willing to accept these values emotionally, then real doctrine will be instilled; doctrine planting stage, at this stage educators can use an emotional approach; exemplary.